How Does Shyness Affect Chinese College Students' Tendency to Mobile Phone Addiction? Testing the Mediating Roles of Social Anxiety and Self-Control - Li, Xinwei; Li, Weijian; Liu, Mengxian; Xiao, Weilong; Zhou, Hui (Frontiers in Public Health, 2022)
Background and Aims: Mobile phone addiction among college students has gained considerable research attention because of its adverse effects on their health and academic performance. However, little is known about the mechanisms underlying the relationship between shyness and mobile phone addiction among college students. Methods: Four questionnaires were used to examine whether mobile phone addiction tendency was predicted by shyness and the mediating roles of social anxiety and self-control among 3,189 Chinese college students. Correlation and mediation analyses were conducted using Hayes PROCESS. Results: The results showed that (1) social anxiety (indirect effect=.22, 95% CI= .18 to .26) and self-control (indirect effect= .23, 95% CI = .21 to .25) played a partial mediating role in the relationship between shyness and mobile phone addiction tendency; (2) social anxiety and self-control also mediated the link between shyness and mobile phone addiction tendency sequentially (indirect effect= 0.10, 95% CI= 0.09 to 0.12). Conclusion: These results suggest that mobile phone addiction among shy college students could be eliminated by alleviating social anxiety and strengthening self-control.